Pendaftaran Hak Cipta Lagu sebagai Objek Jaminan Fidusa - Kadek Arya Oka Sumantara; I Wayan Novy Purwanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Song or Music Copyright with the provisions stipulated in Law Number 42 of 1999 concerning Fiduciary Guarantees, explains that